Expectativa e prática materna do aleitamento exclusivo e a saúde bucal do bebê - Ramirez, Gleice Tibauje Vicente [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The exclusive breastfeeding (EBF) is fundamental for the health of child, however the sucess of the practice isn't always accomplished, because it depends on different determinants. In view of this, the objective of the present study was to verify the expectations of pregnant women in relation to exclusive breastfeeding and the importance of breastfeeding and its relationship with the oral health of the child and then accompany the practice during the first six months of the baby's life for making inquiries and oral examination of the mother and baby. It is a longitudinal study with 74 pairs of mothers and children (n=148). The pregnant women who were in the last trimester of gestation were interviewed about the expectation of the EBF and its relationship with the baby's oral health in the Family Health Units. At six months of age, the mothers were visited at home to verify the practice of EBF and to perform oral examination. It was found that 95.95% of respondents wanted to breastfeed her child; 74% wanted EBF up to six months old baby, however, after six months, 63.51% of mothers were breastfeeding and only 18% were on EBF; 31.05% of the mothers had trouble breastfeeding. Regarding oral health 98.65% of the women wanted to clean the baby's mouth and take him to the dentist; 36.49% lead pacifier to the hospital and 29.73% felt that breastfeeding was not important to the oral health of the baby. After six months of the baby's birth; 63.51% cleared the baby's mouth; 91.89% had not yet taken their babies to the dentist and 25.68% led pacifier to the hospital. Regarding oral health, 32.72% of the mothers had a white spot. Of the total of 74 babies, 16 had teeth at six months of age, three had white spots and were not in EBF. The expectation of exclusive breastfeeding is not has configured in practice and that maternal knowledge relating to oral health...

O aleitamento materno exclusivo (AME) é fundamental para a saúde do bebê, entretanto o sucesso da sua prática nem sempre é alcançado, pois depende de diferentes determinantes. Em vista disto, o objetivo do presente trabalho foi verificar a expectativa das gestantes em relação ao AME, a percepção sobre a importância do aleitamento e a sua relação com a saúde bucal do filho e, posteriormente, acompanhar a prática durante os seis primeiros meses de vida do bebê para realização de inquérito e exame bucal da mãe e do filho. Trata-se de um estudo longitudinal com 74 pares de mães e bebês (n=148). As gestantes que se encontravam no último trimestre de gestação, foram entrevistadas sobre a expectativa do AME e a sua relação com a saúde bucal do bebê, nas Unidades de Saúde da Família. E aos seis meses de idade do bebê, as mães foram visitadas nos domicílios, para verificação da prática do AME e realização de exame bucal. Verificou-se que 95,95% das entrevistadas pretendiam amamentar seu filho; 74% queriam AME até o sexto mês de idade do bebê, entretanto, após seis meses, 63,51% das mães estavam amamentando e apenas 18% estavam em AME; 31,05% das mães tiveram dificuldades para amamentar. Com relação à saúde bucal 98,65% das gestantes pretendiam limpar a boca do bebê e levá-lo ao cirurgião-dentista; 36,49% levariam chupeta ao hospital e 29,73% achavam que amamentar não era importante para a saúde bucal do bebê. Após seis meses do nascimento do bebê; 63,51% limpavam a boca do bebê; 91,89% ainda não haviam levado seus bebês ao cirurgião-dentista e 25,68% levaram chupeta ao hospital. Em relação a saúde bucal, 32,72% das mães possuíam mancha branca. Do total de 74 bebês, 16 possuíam dentes aos seis meses de idade, três apresentavam manchas brancas e não estavam em AME. A expectativa...
Keywords: Aleitamento materno; Saúde bucal; Lactente; Breast feeding